EUFEMISME PADA KOLOM EDITORIAL KORAN TRIBUN PONTIANAK - Apriyani, Tri; Madeten, Sisilya Saman; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study examines the use of euphemism (refinement of meaning) contained in the editorial column of the Tribun Pontianak newspaper from July to September 2018. This research uses a descriptive method with a qualitative research form. Data collection techniques namely documentary studi techniques. Data collection tools namely research and data recording cards. The results showed that the form of euphemism from 47 data presented, obtained data the use of abbreviations as much as 5 data, the use of absorption word as much as 20 data, 3 the use of foreign terms 9 data, the use of metaphor 6 data, the use of 7 data perifrasis. Based on these results it is concluded that the use of uptake is more dominant in the use of euphemism. Then, the benefits of euphemism are obtained for politeness and comfort as much as 22 data, to disguise the meaning of 18 data, to reduce the shame of 6 data, and to carry out religious orders 1 data. Based on these results, it is concluded that the benefits of euphemism for politeness and comfort are more often used in uphemisms.Â Keywords: Form, Editorial, Euphemism, and Benefits.